Factors affecting preregistered nurses' willingness to serve in geriatric long‐term care. Issue 5 (22nd February 2021) - Hsieh, Pei‐Lun; Chen, Ching‐Min; Chen, Hsiao‐Mei; Yang, Fu‐Chi
Abstract: Aim: Rapidly ageing population leads to increased demands for long‐term care. Taiwan's preparation for its ageing population focuses on engaging healthcare professionals. This study explored pre‐registered nurses' current knowledge, experience in geriatric long‐term care (GLTC) and willingness to serve in GLTC. Design: A cross‐sectional survey design and a self‐developed structured questionnaire were used. Methods: A probability proportionate to size sampling strategy was used to collect data from students in junior college and bachelor of nursing science programmes in Taiwan in 2017. Multiple regression was adopted to predict significant factors that influence nursing students' willingness to serve in GLTC. Results: The willingness to serve in GLTC was positively correlated with their experience of living with older adults, practicum experience, taking GLTC‐related courses and interest in GLTC. Willingness to serve older/disabled patients can be enhanced through school courses and practicum experiences, indicating the importance of GLTC‐related courses in the training of the professional nursing workforce.